Perjumpaan Pertama Bangau Storm (Ciconia Stormi) Di PBPH-HA, PT. Ratah Timber - Adies Kuncahyo, Bantista; Harirustaman, Irfan; Wahyudi, Sri; Alita, Ghalibia (Unmuh Babel Press, 2024)
Indonesia as a mega-biodiversity country which is the important value for avian conservation in the world. However, negative issues from activities that causes degradation and forest loss such as logging and land conversion into plantation have been considered a factor in population decline indeed for extinction of a species. The Storm’s Stork (Ciconia stormii, Blastur 1896) is a large water bird that felt the impact so the species is classified as endangered in the Red List of IUCN. The first recorded for the Storm’s Stork in Indonesia’s production forest (PBPH-HA) discovered in PT. Ratah Timber. This is a good news for avian conservation in the world, especially for Indonesia. The records are three individuals in a nest on the RKT block 2019 forest. The nest on banggeris tree (Koompassia excelsa) which is protected by management so banggeris is not included list of logged tree. The Storm’s Stork is extremely secretive so they require habitat characteristics that is primary forest, heavy canopy cover, distance from noisely and nuisance. Therefore, presence of the Storm’s Stork indicated logging activity in PBPH PT. Ratah Timber has implemented and committed for sustainablity forest production management especially for conservation and environmental aspects.Keywords: ciconia stormii; conservation; production forest; ratah timber; storm’s stork